Low Plasma Testosterone is Associated with Elevated Cardiovascular Disease Biomarkers - Pastuszak, Alexander W. (J Sex Med, 2017)
BACKGROUND: The relationship between testosterone (T) plasma concentration and cardiovascular risk is unclear, with evidence supporting increased risk in men with both low and high T levels. Few studies have assessed cardiovascular (CV) risk as a function of plasma T levels using objective biomarkers. AIM: To determine the relationship between T levels and high-sensitivity (hs) CV risk biomarkers. METHODS: 10,041 male patients were identified in the database of a commercial clinical laboratory performing biomarker testing. Patients were grouped by total T concentration and associations with the following biomarkers were determined: cardiac troponin I (cTnI), endothelin-1 (ET-1), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), interleukin-17A (IL-17A), N-terminal pro-B-type natriuretic peptide (NTproBNP), high-density lipoprotein (HDL), hs c-reactive protein (CRP), hemoglobin A1c (HbA1c), and leptin. OUTCOMES: The association of CV risk markers with levels of T in men. RESULTS: The median (interquartile range) age in the cohort was 58 (48, 68) years, and the median plasma T level was 420 (304, 565) ng/dL; T levels did not vary with patient age. An inverse relationship between plasma T levels and CV risk was observed for 9 of 10 cardiovascular markers: cTnI, ET-1, IL-6, TNF-α, NTproBNP, HDL, hsCRP, HbA1c, and leptin. Even after adjusting for age, BMI, HbA1c, hsCRP, and HDL levels, the CV markers IL-6, ET-1, NTproBNP, and leptin were significantly associated with T <250 ng/dL. CLINICAL IMPLICATIONS: Men with low T levels may be at increased risk for increased CVD as seen by elevated CV risk markers. STRENGTH & LIMITATIONS: This study is performed in a group of 10,041 men and is the first study to exam CV risk associated with circulating T levels using a large panel of 10 objective biomarkers. This study is limited by an absence of clinical data indicating if men had preexisting CVD or other CV risk factors. CONCLUSION: Men with low plasma T levels exhibit elevations in CV risk markers, consistent with a potential increased risk of cardiovascular disease.